Purification and Characterization of Glucose-6-phosphate Dehydrogenase from Lake Van Fish (Chalcalburnus tarichii Pallas, 1811) Erythrocytes - OZDEMIR, HASAN; TURKOGLU, VEDAT; CIFTCI, MEHMET (Asian Journal of Chemistry, 2010)
Glucose 6-phosphste dehydrogenase (D-glucose 6-phosphate: NADP+ oxidoreductase, EC 1.1.1.49; G6PD) was purified with 2',5'- ADP Sepharose 4B affinity gel chromatography from Lake Van fish (Chalcalburnus tarichii pallas, 1811) erythrocytes and were investigated some characteristics and kinetics of the enzyme. Purification step of the G6PD were controlled with SDS-PAGE and molecular weight and submolecule was determined by gel filtration chromatography and SDS-PAGE. The activity of enzyme was measured by using Beutler's method. The purification procedure was composed of two steps: hemolysate preparation and 2',5'-ADP Sepharose 4B affinity gel chromatography. The purified enzyme, having the specific activity of 17, 38 EU/mg proteins, was purified 1,100-fold with a yield of 33, 54 %. Optimum pH, optimum temperature and stable pH of the G6PD were 8.5, 40ºC and 8.0, respectively. KM and Vmax values for NADP+ and glucose 6-phosphate (G6-P) were also determined for the enzyme. For NADP+, KM and Vmax value at optimum pH and 25ºC for the G6PD was 0.027 mM and 0.091 EU/mL, respectively. For G6-P, KM and Vmax value at optimum pH and 25ºC for the G6PD was 0.0439 mM and 0.013 EU/mL, respectively.